Assessment of Psychological Impact on the Health Care Workers due to Covid-19 Pandemic in Tertiary Care Hospitals of Karachi - Ali, Shanila Feroz; Mahmood, Kauser; Un Nisa, Zaib; Raza, Muhammad Saad; Zain, Syeda; Udaipurwala, Iqbal Hussain (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To assess the psychological impact of COVID-19 pandemic on health care workers in tertiary care hospitals of Karachi. METHODOLOGY: This is a multi-centric cross-sectional study conducted at tertiary care hospitals of Karachi (Pakistan). Total of 350 health care workers including both males and females, from different private and Government tertiary care hospitals were approached and enrolled after fulfilling the selection criteria from 22 May 2020 till 22 Aug 2020. The semi structured Performa was used for demographic details while Patient health Questionnaire (PHQ-9) and Generalized Anxiety Disorder (GAD 7) were administered for evaluation of depression and anxiety respectively. RESULTS: In this study, out of total 350 participants, 220 (62.8%) has depression while 206 (58.8%) has anxiety. Degree of depression was mild in 81 (23.1%) of health care workers, moderate in59 (16.8%), moderately severe in 50 (14.2%), severe in severe in 30 (8.6%). Similarly, mild anxiety was present in 75 (21.4%), moderate in 74 (21.1%) and severe anxiety in 57 (16.3%) persons. The most common problem they faced is ?Fear of transmission of disease family /close friends? being present in 311 (88.9%) p-value = 0.014 CONLUSION: It is evident that health care workers are affected with depression and anxiety due to pandemic. It is necessary to take appropriate steps in order to manage psychological impact of the stress so that they can be more productive in their respective fields. KEYWORDS: Health care workers; Depression; Anxiety, COVID-19 Patient health questionnaire-9; generalized anxiety disorder-7